ANALISIS STUDI KELAYAKAN BISNIS UMKM PADA COFFEE SHOP PILONA COFFEE DI KOTA TANGERANG - Alfian Adhitama; Nur Fitri Rahmawati; Selvi Selvi (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims to find out about the Culinary Business Feasibility Study at Coffee Shop Pilona Coffee in the 202 periode sighted from financial and non-financial aspects. This research uses a qualitative approach and includes case study research, thus the results of this research are descriptive analysis namely in the form of written or spoken words from the observed behavior especially related to how the culinary business method is carried out at the Coffee Shop in Tangerang City for the 202 period. The results of the research state that the development of the Coffee Shop business owned by Mr. Urip Nursalim is very feasible to carry out and keep running and even developed. Consideration of this feasibility is based on non-financial aspects, namely market aspects and marketing aspects including Product, Price, Place and Promotion, while the financial aspect, namely PP (Payback Period) occurs for 0.5 years or 5 months, NPV > 0, that is Rp. 130,703,893, P value > 1 amounting 3.3 and the IRR value for this investment is 58.5% higher than the interest rate in 2021.